Frequency of Hepatitis C Virus genotypes among non-responders to combination therapy - Gul, Amina (International Journal of Pathology, 2019)
Background: Hepatitis C Virus has been characterized into seven major genotypes and multiple subtypes which display variable distribution across the globe. Accurate identification of Hepatitis C Virus genotypes prior to initiating antiviral therapy plays a vital role in the management of chronic Hepatitis C Virus infected patients. Diverse genotypes of Hepatitis C Virus differ with respect to treatment response, nature as well as duration of therapy. Due to treatment associated side effects and high costs, Hepatitis C Virus genotype determination especially among non-responders is required to help these patients in selection of appropriate antiviral therapy.Objectives: The aim of this study was to find out the frequency of HCV genotypes among non-responders to combination therapy.Patients and Methods: This descriptive study was carried out at Institute of Basic Medical Sciences, Khyber Medical University Peshawar from January 2016 to June 2016 after institutional ethical approval. Serum samples were collected from 110 chronic HV infected patients who failed to respond to either Conventional or Pegylated Interferon therapy. Identification of HCV genotype was performed using two sets of newly designed primers in a modified type specific nested PCR based genotyping assay. Agarose gel electrophoresis was carried out for identification of genotype specific PCR product. Results: Among 110 actively infected samples, majority (53.4%) of the infections were attributed to HCV genotype 3a. Among other subtypes, HCV 1b (17.1%) and 1a (9.4%) genotypes were predominantly observed. HCV 3b, 2a and 2b accounted for infection in 8.2%, 5.4% and 3.3% of the patients respectively. Mixed infections with more than one type in a single specimen were found in 2.1% of the isolates, while 1.1% of the samples remained untypeable.Conclusion: The current study reports a high frequency of Hepatitis C Virus 3a among studied isolates. Emerging resistance against antiviral therapy might be attributed to HCV 1b, 1a and other subtypes observed among non-responders.